Theoretical evaluation of the ability to process on the rational unified process Moprosoftx - Canepa Vega, Katia (2010)
Determining the processes capabilities in companies that develop software is an issue that has gained interest because through them they can be classifi ed at a certain level of capability or maturity, depending on the model used. In addition, some companies have a set of established practices and working methods, in the case of Peru is often based on Rational Unifi ed Process (RUP). This paper presents the theoretical evaluation of the processes capabilities in the operation category of software processes model Moprosoft under the assumption that an organization has properly implemented a set of minimal elements of RUP.